Land Capability for Cattle-Farming in the Merapi Volcanic Slope of Sleman Regency Yogyakarta - Rini Widiati; Nafiatul Umami; Totok Gunawan (Faculty of Geography, Universitas Gadjah Mada, 2017)
This research carried out to study the cattle farming development based on the land capability in rural areas of the Merapi Volcanic slope of Sleman Regency Yogyakarta after eruption 2010. Samples taken were Glagaharjo village (Cangkringan Sub-District) as impacted area and Wonokerto village (Turi Sub-District) as unimpacted area. Survey method used were to land evaluation analysis supported by Geographic Information System (GIS) software. Materials used were Indonesian topographical basemap (RBI) in 1:25000 scale, IKONOS image [2015], land use map, landform map, and slope map as supple- ments. Potential analysis of land capability for cattle forage using the production unit in kg of TDN per AU. The result showed that based on the land capability class map, both villages had potential of carrying capacity for forage feed that could still be increased as much as 1,661.32 AU in Glagaharjo and 1,948.13 AU in Wo n o k e r t o